ADOPSI SISTEM INFORMASI AKUNTANSI PADA USAHA KECIL DAN MENENGAH: SUDAHKAH SELARAS? STUDI EMPIRIS PADA USAHA KECIL DAN MENENGAH DI SURABAYA DAN SEKITARNYA - Agnes Utari Widyaningdyah (Jurnal Keuangan dan Perbankan, 2014)
This study aims to investigate the alignment between Accounting Information Systems ( AIS ) and the business strategy as well as the factors that can influence the alignment of the Small and Medium Enterprises ( SMEs ) in surrounding Surabaya. Cluster analysis is used to find two sets of groups which could be considered more aligned and less aligned. By using chi - square and independent sample t – test, alignment’s score of AIS for both groups is tested on some factors, such as, the complexity of information technology , knowledge and commitment of the manager / owner, the existence of external and internal experts, and the size of the company . The results indicates that the complexity of information technology, knowledge of manager / owner, and the existence of internal experts relates to the AIS alignment in SME’s surrounding Surabaya.